Augmenting Plasticity Induction in Human Motor Cortex by Disinhibition Stimulation - Cash, Robin F.H. (Cereb Cortex, 2016)
Cellular studies showed that disinhibition, evoked pharmacologically or by a suitably timed priming stimulus, can augment long-term plasticity (LTP) induction. We demonstrated previously that transcranial magnetic stimulation evokes a period of presumably GABA(B)ergic late cortical disinhibition (LCD) in human primary motor cortex (M1). Here, we hypothesized that, in keeping with cellular studies, LCD can augment LTP-like plasticity in humans. In Experiment 1, patterned repetitive TMS was applied to left M1, consisting of 6 trains (intertrain interval, 8 s) of 4 doublets (interpulse interval equal to individual peak I-wave facilitation, 1.3–1.5 ms) spaced by the individual peak LCD (interdoublet interval (IDI), 200–250 ms). This intervention (total of 48 pulses applied over ∼45 s) increased motor-evoked potential amplitude, a marker of corticospinal excitability, in a right hand muscle by 147% ± 4%. Control experiments showed that IDIs shorter or longer than LCD did not result in LTP-like plasticity. Experiment 2 indicated topographic specificity to the M1 hand region stimulated by TMS and duration of the LTP-like plasticity of 60 min. In conclusion, GABA(B)ergic LCD offers a powerful new approach for augmenting LTP-like plasticity induction in human cortex. We refer to this protocol as disinhibition stimulation (DIS).